Production of cellulase enzyme from Aspergillus terreues SUK-1 using sugar cane waste : the effect of substrate concentration and assay temperature - Mohd. Nazip, Kassebullah (2006)
Natural by product of agricultural waste can be turned to products of commercial interests such as ethanol, glucose and single cell protein. Much effort from scientists and researches all around the world has been put to extend the full use of agricultural waste. Reports of cellulase enzyme production from the bioconversion of lignocellulosics materials has much been made. However there is still much space to find the most suitable condition. In this research, sugar cane bagasse which is used as substrate is subjected to physical treatment using milling and grinding. After that, sugar cane bagasse is use as substrate in the production of cellulase enzyme using Aspergillus terreus SUK-1 fungus. Cellulase enzyme production was studied using submerged fermentation under shaking. The production was run in a lab scale using Erlenmeyer flask only. After that the enzyme was assayed at different temperature. The purpose of this research was to investigate the effect of substrate concentration on yield of cellulase and the optimum temperature where the yield of enzyme was the highest. Analysis is based on the activity of carboxymethylcellulase and xylanase enzymes. Result shows that the peak of xylanase activities was 0.011322 U/ml on day 5 using 5g SCB as substrate and fermentation temperature of 50°C while carboxymethylcellulase peak was 0.007985049 U/ml of activity using 3g SCB as substrate and fermentation temperature of 40°C. Xylanase activity was high when assayed at 50°C while carboxymethylcellulase activity was high when assayed at 40°C.